Involvement of ICAM‐1 in impaired spermatogenesis after busulfan treatment in mice. (25th March 2015) - Cai, Y.; Liu, T.; Fang, F.; Shen, S.; Xiong, C.
Summary: Expression of adherence proteins, such as P‐cadherin, has been identified in the normal testis and changed in impaired testis induced by alkylating agents. Intercellular adhesion molecule‐1 (ICAM‐1), a member of the immunoglobulin superfamily of cell adhesion molecules, is a constituent component of the blood–testis barrier and a multifunctional molecule in homeostasis of spermatogenesis. However, the distribution of ICAM‐1 in the testis of mice and expression changes after busulfan treatment remain unclear. In this study, ICAM‐1 immunoreaction was detected in Sertoli and germinal cells, particularly in spermatogonia, and elongating and elongated spermatids of normal testes. Accompanied with degeneration of spermatogenesis (decrease in testicular and epididymal weights, as well as loss of germ cells in histological morphology), ICAM‐1 expression declined significantly in the seminiferous tubules during a 4‐week experimental period, particularly in the first 2 weeks (40 mg kg −1 busulfan, single injection). Compared with the control group, busulphan‐treated testes showed a significant increase in lipid peroxidation during weeks 1 and 2. Thus, ICAM‐1 may play an important role in the homeostasis of spermatogenesis, and busulfan treatment can lead to adhesion disintegration.